2022
DOI: 10.1007/s00401-022-02516-2
|View full text |Cite|
|
Sign up to set email alerts
|

Amplification of the PLAG-family genes—PLAGL1 and PLAGL2—is a key feature of the novel tumor type CNS embryonal tumor with PLAGL amplification

Abstract: Pediatric central nervous system (CNS) tumors represent the most common cause of cancer-related death in children aged 0–14 years. They differ from their adult counterparts, showing extensive clinical and molecular heterogeneity as well as a challenging histopathological spectrum that often impairs accurate diagnosis. Here, we use DNA methylation-based CNS tumor classification in combination with copy number, RNA-seq, and ChIP-seq analysis to characterize a newly identified CNS tumor type. In addition, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 68 publications
3
15
0
Order By: Relevance
“…In the CNS, gains and amplifications of these genes have also been reported in gliomas, and it has been evidenced that PLAGL2 promotes renewal of neural stem cells/ progenitor cells by inhibiting their differentiation and thus promoting gliomagenesis [31]. Similarly to the two specimens in the current study, the reported cases with PLAGL2 amplification mainly affected infants and were supratentorial [28,32]. This case and ours presented an amplification of the PLAGL2 gene.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In the CNS, gains and amplifications of these genes have also been reported in gliomas, and it has been evidenced that PLAGL2 promotes renewal of neural stem cells/ progenitor cells by inhibiting their differentiation and thus promoting gliomagenesis [31]. Similarly to the two specimens in the current study, the reported cases with PLAGL2 amplification mainly affected infants and were supratentorial [28,32]. This case and ours presented an amplification of the PLAGL2 gene.…”
Section: Discussionsupporting
confidence: 75%
“…Radiologically, they appear as a solid and cystic peri-or intraventricular mass with an intermediate restriction of the diffusion, high perfusion value, and an intense enhancement following gadolinium injection. Histopathologically, the tumors are well-circumscribed with a branching capillary network, but without microvascular proliferation, as previously described [28]. The tumor cells are monotonous without a distinct pattern of differentiation.…”
Section: Discussionsupporting
confidence: 65%
“…Recently, a subset of embryonal brain tumors was found to be defined by amplification and overexpression of PLAGL2, and our study expands on its oncogenic importance [73].…”
Section: Discussionmentioning
confidence: 52%
“…Recently, a subset of embryonal brain tumors was found to be defined by amplification and overexpression of PLAGL2 , and our study expands on its oncogenic importance [73]. PLAGL2 was initially described as a homolog of the PLAG1 transcription factor, whose translocation-driven overexpression defines pleomorphic adenoma of the salivary glands [74].…”
Section: Discussionmentioning
confidence: 83%
“…2021), sometimes classified by sturgeon as a SUBEPN. PMC_88; low grade glioma with a PLAG amplification (Keck et al . 2022), Sturgeon does not reach the 0.8 threshold in this sample, but we note that the highest scoring class is often Medulloblastoma Group 3.…”
Section: Resultsmentioning
confidence: 99%